2009
DOI: 10.2174/1874912700902010058
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Profile and Socio-Economic Status of Saharia, a Primitive Tribe of India

Abstract: A study was conducted among Saharia, a primitive tribe of central India, with an objective to assess the nutritional profile and associated socio-economic factors. A cross sectional sample of 364 adult males and females aged 18-60 years was studied. Stature, body weight, skinfold thickness, circumferences, fat percent, grip strength and blood pressure were measured on each subject. Body mass index, Trunk extremity ratio and Grand mean thickness were computed statistically. A higher percentage of chronic energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…A higher prevalence of CED as well as overweight among males in comparison to females reflects the higher sensitivity in terms of BMI to their environment. It was also observed that the level of undernutrition on the basis of MUAC was higher among Saharia females (Kapoor et al 2009). In the present study, we also found a relationship between socio-economic status and nutritional status.…”
Section: Discussionsupporting
confidence: 83%
“…A higher prevalence of CED as well as overweight among males in comparison to females reflects the higher sensitivity in terms of BMI to their environment. It was also observed that the level of undernutrition on the basis of MUAC was higher among Saharia females (Kapoor et al 2009). In the present study, we also found a relationship between socio-economic status and nutritional status.…”
Section: Discussionsupporting
confidence: 83%
“…BMI is most commonly used measure of overweight, obesity as well as of CED (chronic energy deficiency) [32,33] and has been found to be important risk factor for CVD [34]. In the present study also BMI was found to be a greater risk factor for cardiovascular health among Jain females supported by strong correlation of BMI with blood pressure, high ' ' value and high odds ratio for hypertension in obese females.…”
Section: Discussionsupporting
confidence: 68%
“…BMI and MUAC have been used as forecasters of subnutrition, intensively in numerous studies (Kapoor et al, 2009;. But arm circumference, a sensitive measure of the loss of muscle mass in the elderly is related to greater degrees of malnutrition than BMI and is validated as nutritional screening tool for malnutrition in the elderly (Chumlea et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Body mass index (BMI) is one of the most established anthropometric indicators used not only for assessment of adult nutritional status but also for the socio-economic condition of a population, especially in developing countries. Mid upper arm circumference (MUAC) is another anthropometric measure, is particularly effective in the determination of malnutrition among adults in developing countries (Shetty et al, 1994;James et al, 1994 ;Khongsdier, 2002;Kapoor et al, 2009). There has been much interest in the literature on the use of skinfolds and derivatives of these for nutritional assessment of muscle and fat body reserves along with its association to chronic (Shetty et al, 1994; Hence, the objective of our research is to understand the role of skinfold thicknesses (taken at various sites over the body) as indicators, to infer the nutritional status of undernourished tribal males of India and to find the best prognosticator skinfold for assessing undernutrition.…”
Section: Introductionmentioning
confidence: 99%